Shots in the Dark : Japan, Zen, and the West - Yamada, Shōji, 1963- (Buddhism and modernity., 2011)
In the years after World War II, Westerners and Japanese alike elevated Zen to the quintessence of spirituality in Japan. Pursuing the sources of Zen as a Japanese ideal, Shoji Yamada uncovers the surprising role of two cultural touchstones: Eugen Herrigel's Zen in the Art of Archery and the Ryoanji dry-landscape rock garden. Yamada shows how both became facile conduits for exporting and importing Japanese culture.